The eye and the whip: corruption control in the Americas - Lagunes, Paul (Oxford University Press, 2021)
"Corruption vulnerabilities exist where government officials have power over the provision of goods and the imposition of costs. Building permits and infrastructure contracts are examples of state-issued goods. Traffic tickets and tax liabilities are examples of costs levied by the state. These and other corruption vulnerabilities turn to actual threats when officials calculate that the benefits of abusing their power are greater than the penalties associated with getting caught. By a similar logic, the formula for corruption control requires increasing the probability of detecting corruption (that is, of activating the eye) through enhanced monitoring and then credibly threatening to apply the appropriate penalty in response to wrongdoing (cracking the whip). Notably, the common policy response to corruption often emphasizes only the first of the two mechanisms. Governments prioritize transparency measures but avoid the risks associated with confronting corruption. Therefore, as a means to improve on the current state of affairs, this book examines distinct approaches to promoting accountability, especially accountability among the set of unelected officials responsible for regulating the built environment. It analyzes the results of field experiments on corruption control conducted in the City of Querétaro in central Mexico, urban and peri-urban districts in Peru, and two of New York City's boroughs. The book contributes evidence-based recommendations for how societies can go about fighting bureaucratic corruption"--